Lexico-semantic group stability ofmodern english nouns - Kalynovska, Iryna; Калиновська, Ірина (Східноєвропейський національний університет імені Лесі Українки, 2014)
Stability is known to be one of the features of linguistic norm, along with a tendency to differentiate variant realizations functionally and stylistically. At the syntactic level linguistic norm is sufficiently stable. Its evolutional development is conditioned by the requirements of social communication, with significant changes that occur not in the set of syntactic means but in the way and frequency of their usage. The following article focuses on the main aspects of lexico-semantic group stability of high frequency Modern English nouns, being the heads of noun phrases used in English literary texts. The analysis is made with the help of statistic formulas of variation coefficient (V) and standard deviation (σ). The investigation reflects a widespread in language and speech preference law, according to which a small amount of units is used very often and carries a maximum functional capacity. The lower the variation coefficient of a language unit, the higher the language unit stability. According to that approach linguistic norm represents constructions that are actually used in language. Відомо, що стабільність є однією з особливостей мовної норми поряд із тенденцією до диференціації варіантних реалізацій у функціонально-стилістичному аспекті. На синтаксичному рівні мовна норма досить стійка. Її еволюційний розвиток зумовлений потребами суспільної комунікації, причому значні зміни відбуваються не в самому наборі синтаксичних засобів, а в способі й частоті вживання цих засобів. Ідеться про основні аспекти стійкості лексико-семантичних груп найчастотніших іменників сучасної англійської мови, які є ядрами іменникових фраз у текстах англомовної художньої прози. Аналіз проводимо за допомогою статистичних формул коефіцієнта варіації (V) та стандартного відхилення (σ). Дослідження є підтвердженням поширеного в мові й мовленні закону переваги, згідно з яким невелика кількість одиниць уживається дуже часто та несе максимум функціонального навантаження. Чим нижчий коефіцієнт варіації, тим більша стабільність уживання мовної одиниці. За такого підходу мовна норма відображає конструкції, які реально використовують у мові.
Стійкість лексико-семантичних груп іменників сучасної англійської мови.
Keywords: language norm; stability; lexico-semantic group; noun phrase; мовна норма; стабільність; лексико-семантична група; іменникова фраза